Synthesis and Optical Properties of ZnO Nanoneedles Array - Tang, B.; Zhang, Q.; Luo, Q.; Wu, Z.H.; Qiu, Y. (Asian Journal of Chemistry, 2014)
Zinc oxide nanoneedles array were synthesized on Si substrate by catalyst-free chemical vapor deposition technique. Scanning electron microscopic images displayed that the ZnO nanoneedles with average diameter of 100 nm were aligned well on Si substrate. TEM images showed that there were some steps on the top of ZnO nanoneedles. Only (002) diffraction peak of ZnO can be found in the XRD patterns of the samples, indicating that the as-grown nanoneedles are highly crystalline in nature and grow along the [0001] direction. The growth mechanism of ZnO nanoneedles array is consistent with step kinetics and bizarre surface growing and the crystal growth is a typical simple-two-dimensional-nucleation normal-layer-growth. Room-temperature photoluminescence spectrum of ZnO nanoneedles array showed two near band-edge emission peaks at 380 and 389 nm and a deep level emission around 480 nm.